The future of police reform: the U.S. Justice Department and the promise of lawful policing - Walker, Samuel (New York University Press, 2024)
"This book is the first thorough study of the Justice Department's pattern or practice program, examining how the program works, how court-imposed consent decrees implement needed reforms, and discussing the various challenges the program has encountered over nearly thirty years"--